Characteristics of Physics Module about Mechanics-Based on Multi Representation to Improve Students of Senior High School Reasoning Ability - Dimas Fawahid Tamimi Anwar; I Ketut Mahardika; Supeno Supeno (Pancaran Pendidikan, 2017)
This study is about the characteristics of Physics Module to improve students of Senior High School reasoning ability-based on Multi-representation. The problem of the study is how characteristics of Physics Modules Based on Multi-representation to improve students ability to reason? This problem is described in two study questions. First, is the Physics Module based on Multi-representation contains examples of the application context of the image phenomenon of physics? Second, how is the writing pattern of Physics Module? This study is about Physics module development based on Multi-representation, using the mix method model of investigation that collecting qualitative data, then construct the draft Module Physics, so the Module Physics ready to be validated. Subjects in this study is a Physics module which can improve the reasoning ability of students in Senior High School. While respondents were Senior High School students majoring in science at the students in Senior High School. Data collection techniques are observations, questionnaires, and documents. Data described in qualitative research. The results showed that the physics module based on Multi-representation contains examples of application of the principle of material in the context of the image physical phenomenon ; and has a certain writing pattern, which has a chapter title sequence, sub-chapter title, instructions for use, a description of the material, sample questions, questions test capabilities, and bibliography.